The effect of recording site on extracted features of motor unit action potential. Issue 129 (June 2016) - Artuğ, N. Tuğrul; Goker, Imran; Bolat, Bülent; Osman, Onur; Kocasoy Orhan, Elif; Baslo, M. Baris
Graphical abstract: Highlights: We simulated five motor units for normal, neurogenic and myopathic cases. We investigated the effect of recording sites on electromyography signals. Myopathic cases demonstrated the most prolonged phase duration near the tendon. Highest number of peaks are observed near the tendon in myopathic conditions. A new feature referred as number of peaks × spike duration was defined. Abstract: Motor unit action potential (MUAP), which consists of individual muscle fiber action potentials (MFAPs), represents the electrical activity of the motor unit. The values of the MUAP features are changed by denervation and reinnervation in neurogenic involvement as well as muscle fiber loss with increased diameter variability in myopathic diseases. The present study is designed to investigate how increased muscle fiber diameter variability affects MUAP parameters in simulated motor units. In order to detect this variation, simulated MUAPs were calculated both at the innervation zone where the MFAPs are more synchronized, and near the tendon, where they show increased temporal dispersion. Reinnervation in neurogenic state increases MUAP amplitude for the recordings at both the innervation zone and near the tendon. However, MUAP duration and the number of peaks significantly increased in a case of myopathy for recordings near the tendon. Furthermore, of the new features, " number of peaks  ×  spike duration " was found as the strongest indicator of MFAP dispersion in myopathy. MUAPs were also recorded from healthy participants in order to investigate the biological counterpart of the simulation data. MUAPs which were recorded near to tendon revealed significantly prolonged duration and decreased amplitude. Although the number of peaks was increased by moving the needle near to tendon, this was not significant.